Analisis Kontribusi, Efektivitas dan Pertumbuhan Pajak Daerah dan Retribusi Daerah Terhadap PAD Kabupaten/Kota di Kalimantan Selatan Tahun 2011 - 2020 - Jirina, Dita; Suherty, Lina (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine the level of contribution, effectiveness, and growth of local tax revenue and regional levies on the local income of districts/cities in South Kalimantan. The method used is descriptive quantitative with analysis technique of contribution ratio, effectiveness ratio, and growth ratio using secondary data from the Directorate General of Fiscal Balance, Ministry of Finance website. This study's results indicate that local taxes' contribution to local revenue has quite good criteria, and local levies to local revenue have poor bars. The effectiveness ratio shows that the average regional tax and regional retribution are very effective. Based on the results of the average regional tax growth rate for 2011-2020 with the criteria of not being successful and the average growth of provincial levies with the requirements of being unsuccessful.